Action research on the effectiveness of a stress management program for nursing students - Arcilla, Vanessa Laura S. (Animo Repository, 2012)
The study sought to determine the perceived stressors of Senior Nursing students (N=107) and the effectiveness of a stress management program that is aligned with the reported stressors in lessening their stress levels. A Stress Identification Sheet was provided and filled out by the students as a survey in gathering data about their stress concerns while Rapid Stress Assessment (Cherewatenko, 2005) was used to measure the stress levels of the students before and after undergoing the stress management program. The study used pretest-posttest ait listed control group design. In the case of students, stress is mostly related to academic experiences. Majority of the identified stressors by the participants falls under the Studies area. Results showed that there is a significant decrease in the stress level of the experimental group after undergoing the program while there is no significant difference in the stress level of the control group. Also, there is a significant difference between the posttest scores of the two groups. Feedback from twenty participants of the experimental group revealed that the program has affected them positively. It is concluded that the stress management program developed for the students is a good way to effectively help them cope with stressful situations they encounter.